One-dimensional simulation of a diesel engine operating with biodiesel - Mohd Rizal, Shafie (2010)
This study is to explore one-dimensional simulation for four cylinders diesel engine. The simulation and computational development of modelling for the research is used the commercial Computational Fluid Dynamics (CFD) of GT-SUITE 6.1 software. The engine model was developed corresponding to a 2.0 litre Mitsubishi 4D68 four-cylinder diesel engine. The diesel engine is simulated to study the characteristic of engine performance when the engine is operating with biodiesel as an alternative fuel. The development of one-dimensional simulation modelling covers full engine cycle consisting of intake, compression, power and exhaust system. For the fuel used which is biodiesel, the database of biodiesel need to be determined because there is no available database for one-dimensional simulation. The results obtained from simulation were compared with the data from the diesel engine operating with conventional diesel. Then, the results gained for biodiesel simulation is compared to experiment to gain more information about its trend. The simulation results showed that the brake power and brake torque were reduced if the diesel engine was being fuelled with biodiesel. Using biodiesel also decrease brake thermal efficiency. The decrease of low heating value resulted to increase brake specific fuel consumption.